2005
DOI: 10.4028/www.scientific.net/msf.488-489.431
|View full text |Cite
|
Sign up to set email alerts
|

Development of Strip Casting Process for Fabrication of Wrought Mg Alloys

Abstract: AZ31 and experimental ZMA611 alloys were strip cast into 2 mm thick strips. The as-cast AZ31 alloy strip consists of columnar dendrites. On the other hand, as-cast ZMA611 alloy strip shows equiaxed dendritic structure through the thickness of strip. Strip cast AZ31 alloy in H24 condition has equivalent yield and tensile strengths with similar ductility compared to commercial ingot cast AZ31-H24 alloy, indicating that strip casting is a viable process for the fabrication of Mg alloy strips. The ZMA611 alloy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Figure 1(a) shows the cross-sectional micrographs of TRC AZ31-0.7Ca alloy in as-cast condition. The as-cast microstructure of AZ31-0.7Ca alloy sheet is similar to that of the previously studied TRC AZ31 alloy, having a similar freezing range [8,9]. Closer examination of the as-cast microstructure shows that it consists of α-Mg dendrite and interdendritic phases.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…Figure 1(a) shows the cross-sectional micrographs of TRC AZ31-0.7Ca alloy in as-cast condition. The as-cast microstructure of AZ31-0.7Ca alloy sheet is similar to that of the previously studied TRC AZ31 alloy, having a similar freezing range [8,9]. Closer examination of the as-cast microstructure shows that it consists of α-Mg dendrite and interdendritic phases.…”
Section: Methodsmentioning
confidence: 62%
“…However, there is a lack of competitive Mg wrought products, especially sheet materials, which are much needed for numerous weight-sensitive applications. The recent development of twin-roll casting (TRC) technology has shown that it can efficiently produce low cost, high quality Mg sheet products that have equivalent mechanical properties to conventional ingot cast Mg alloys [7][8][9][10][11][12]. The TRC process combines casting and hot rolling into a single step, giving the advantage of one-step processing of flat rolled products.…”
Section: Introductionmentioning
confidence: 99%
“…1. The microstructure of as-cast Mg-4Zn-1Gd alloy shows a development of inclined columnar dendritic microstructure, similar to the microstructure of commercial AZ31 alloy subjected to TRC [28]. After homogenization treatment at 697 K for 4 hours, the microstructure reveals uniform microstructure having an average grain size of 16.3 μm.…”
Section: Resultsmentioning
confidence: 77%
“…The tensile properties of the specimen pre-heated for 30 min after annealing are quite similar to those of AZ31 in H24 condition (partially annealed). 7) On the other hand, specimen pre- heated for 12 h after annealing shows quite large elongation of 27%. Larger elongation of the specimen pre-heated for 12 h than that of specimen pre-heated for 30 min after annealing indicates the importance of morphology of second phase particles in affecting tensile properties, particularly elongation.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…5) It has been recently shown that the application of twin-roll casting (TRC) can effectively produce low cost Mg alloy sheets with the equivalent tensile properties to those of conventionally processed alloy sheets. [6][7][8][9] Due to its relatively fast solidification rate, TRC can provide beneficial effects on microstructure such as refinement of microstructural features, extension of solid solubilities, and formation of metastable or non-equilibrium phases. 3,10) Among various Mg alloy systems, Mg-Zn-Y alloys are quite interesting since they can incorporate novel second phase particles such as icosahedral phase 11) or long period ordered (LPO) structure 12) depending on Zn/Y ratio.…”
Section: Introductionmentioning
confidence: 99%